EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION DAN RECIPROCAL TEACHING PADA MATERI BANGUN RUANG DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI SE-KABUPATEN WONOGIRI TAHUN PELAJARAN 2013/2014 - Mahendrawan, Ersam; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed to know: (1) which one of the learning models gave a better achievement between problem based instruction, reciprocal teaching, or conventional, (2) which one of the students with types of learning style had a better achievement between students with visual, auditory, or kinesthetic, (3) at each learning style types, which one of the learning models gave a better achievement between problem based instruction, reciprocal teaching, or conventional, (4) at each the learning models, which one of the students with types of learning style had a better achievement between students with visual, auditory, or kinesthetic. The population of the research was the eighth class students of Junior High School at Wonogiri regency on academic year 2013/2014 and the sample was students from SMP Negeri 1 Slogohimo, SMP Negeri 1 Jatipurno and SMP Negeri 4 Jatisrono which was taken by using stratified cluster random sampling technique. This was a quasi-experimental research with a 3x3 factorial design. The data analysis technique used was unbalanced two ways analysis of variance. Based on the data analysis, it was concluded as follows. 1) Problem based instruction gave better achievement than reciprocal teaching, conventional gave the same achievement as problem based instruction and reciprocal teaching, 2) The students with visual had better achievement than the students with auditory and kinesthetic, the students with auditory had better achievement than students with kinesthetic, 3) At the students with visual, reciprocal teaching gave the same achievement as problem based instruction and conventional, problem based instruction gave better achievement than conventional. At the students with auditory, problem based instruction gave better achievement than reciprocal teaching, conventional gave better achievement than reciprocal teaching and gave the same achievement as problem based instruction. At the students with kinesthetic, problem based instruction gave the same achievement as reciprocal teaching and conventional, 4) In reciprocal teaching, the students with visual had better achievement than the students with auditory, the students with kinesthetic had the same achievement as the students with visual and auditory. In problem based instruction, the students with visual had the same achievement as the students with auditory and had better achievement than the students with kinesthetic, the students with auditory had better achievement than the students with kinesthetic. In conventional model, the students with visual had the same achievement as the students with auditory and kinesthetic.Keywords: Problem Based Instruction, Reciprocal Teaching, Learning Style, Achievement.